2008
DOI: 10.2337/db07-1065
|View full text |Cite
|
Sign up to set email alerts
|

HNF4α and the Ca-Channel TRPC1 Are Novel Disease Candidate Genes in Diabetic Nephropathy

Abstract: OBJECTIVE-The nuclear receptor hepatic nuclear factor 4␣ (HNF4␣) is a master regulatory protein and an essential player in the control of a wide range of metabolic processes. Dysfunction of HNF4␣ is associated with metabolic disorders including diabetes. We were particularly interested in investigating molecular causes associated with diabetic nephropathy.RESEARCH DESIGN AND METHODS-Novel disease candidate genes were identified by the chromatin immunoprecipitation-cloning assay and by sequencing of immunopreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…A previous study by Xie et al (54) reported that levels of HNF4␣ protein and mRNA were decreased in the liver of db/db mice (type II diabetes model) but increased in streptozotocin-treated mice (type I diabetes model). A recent study by Niehof and Borlak (32) showed that HNF4␣ protein expression was repressed in kidneys of both diabetic rats and humans and that the reduced HNF4␣ might contribute to diabetic nephropathy by inhibiting canonical transient receptor potential (TRP)C1 protein in the kidney (32). Since TRPC1 is a Ca 2ϩ -permeable channel expressed in kidney cells (10), the results of Niehof and Borlak's study suggest that HNF4␣ may affect diabetic renal changes by regulating renal cell Ca 2ϩ signaling.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…A previous study by Xie et al (54) reported that levels of HNF4␣ protein and mRNA were decreased in the liver of db/db mice (type II diabetes model) but increased in streptozotocin-treated mice (type I diabetes model). A recent study by Niehof and Borlak (32) showed that HNF4␣ protein expression was repressed in kidneys of both diabetic rats and humans and that the reduced HNF4␣ might contribute to diabetic nephropathy by inhibiting canonical transient receptor potential (TRP)C1 protein in the kidney (32). Since TRPC1 is a Ca 2ϩ -permeable channel expressed in kidney cells (10), the results of Niehof and Borlak's study suggest that HNF4␣ may affect diabetic renal changes by regulating renal cell Ca 2ϩ signaling.…”
mentioning
confidence: 76%
“…Previous studies revealed that HNF4␣ regulates "drug" transporters during development of the kidney proximal tubule (15,29), stimulates the mesenchymal-epithelial transition in early nephrogenesis (24), and suppresses renal cell carcinoma (28). Recently, Niehof and Borlak (32) reported that HNF4␣ protein was significantly reduced in kidneys from diabetic rats and humans. The decrease in HNF4␣ in the diabetic kidney downregulated expression of TRPC1 protein, a Ca 2ϩ channel that regulates Ca 2ϩ signals in kidney cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest to the question of the cellular basis of high glucose (HG)-induced endothelial dysfunction is the report from Kumar et al (28) that an increase in vascular smooth muscle TRPC1 expression was associated with enhanced Ca 2ϩ entry in human and animal vascular injury models and that the vascular injury associated with enhanced Ca 2ϩ entry was reduced by an isoform-specific antibody against TRPC1. Finally, the TRPC1 gene, localized on human chromosome 3q22-24, a region closely associated with diabetic nephropathy, has been identified as a possible candidate gene in diabetic nephropathy (35).…”
mentioning
confidence: 99%
“…There is evidence that HNF4α gene expression is reduced in the kidney of patients with diabetic nephropathy (Niehof and Borlak, 2008) (Nitsch et al, 1993;Nishiyori et al, 1994), we considered that HNF4α could play a role in the transcriptional control of mALT gene.…”
Section: Discussionmentioning
confidence: 99%